Anticancer Podophyllotoxin Recovery from Juniper Leaves at Atmospheric and High Pressure Using Eco-Friendly Solvents - Diana Ivanova; Paraskev Nedialkov; Alexander Tashev; Zlatina Kokanova-Nedialkova; Marta Olech; Renata Nowak; Stanislava Boyadzhieva; George Angelov; Dragomir Yankov (Plants, 2023)
Podophyllotoxin (PPT) is a precursor for the synthesis of drugs against cancer and other diseases. The present sources of PPT (Sinopodophyllum hexandrum and Podophyllum peltatum) are endangered species, with PPT production highly dependent on their growing conditions. In connection with the identification of new sources of PPT, the present study aimed to recover PPT from Juniperus virginiana leaves via atmospheric or high pressure extraction methods with a focus on using eco-friendly solvents. PPT quantification was determined by UHPLC/HRMS/MS. A thorough study of conventional extraction was carried out to reveal the optimal conditions (solvent ethyl acetate at room temperature and a duration of 1 h) for maximizing the PPT recovery (about 30 mg/g of dry extract and 3 mg/g of dry initial plant material). Peleg’s equation was applied for process kinetics modeling. The best PPT content in the final dry extract (42–45 mg/g of dry extract) was obtained by high pressure methods under supercritical (scCO2 with ethanol or ethyl acetate, 30 MPa, 50 °C and 100 min) or accelerated solvent extraction conditions (solvent ethyl acetate, 10.35 MPa, 20 °C and 3 cycles for 15 min). Seasonal stability and storage stability of the raw material were also determined. The present results have potential applications in the pharmacy for the delivery of PPT from juniper leaves.